Molecular characterisation of Diffuse large B-cell lymphomas (DLBCL) diagnosed at Groote Schuur Hospital (GSH) - Watson, Trischke (Department of Pathology, 2025)
Background: Diffuse large B-cell lymphoma (DLBCL) is an aggressive high-grade neoplasm characterised by a diverse spectrum of clinical, morphological, immunophenotypic, and molecular features and response to therapy and survival. It is the most common lymphoma subtype diagnosed in South Africa. While the exact pathogenesis of DLBCL is not fully understood, genetic alterations in oncogenes such as MYC, BCL2 and BCL6 as well as viral oncogenes, contribute to its development and progression. In the World Health Organisation (WHO) classification of haematolymphoid tumours, the classification of DLBCL requires testing for MYC, BCL2 and BCL6 genetic alterations to determine subtypes such as DLBCL with MYC and BCL2 rearrangements (“double-hit”) or DLBCL with rearrangements of MYC and BCL2 with BCL6 rearrangement (“triple-hit”). Cases without rearrangements, single rearrangements or copy number variation (CNV) are classified as DLBCL, Not Otherwise Specified (NOS). Double-hit (DHL) or triple-hit (THL) lymphomas typically have a worse prognosis and outcome compared to DLBCL, NOS. Fluorescence in-situ hybridisation (FISH) is the gold standard cytogenetic method for detecting specific genetic alterations (rearrangement, gain, amplification, and loss) in cancer cells. Our centre's current diagnostic workup of DLBCLs does not include FISH for MYC, BCL2 and BCL6. This information is not only necessary for the classification of DLBCLs but is also critical for patient prognosis and treatment decisions. Aim and Objective: This study aimed to determine the profile of MYC, BCL2 and BCL6 gene alterations in a cohort of DLBCL cases diagnosed at Groote Schuur Hospital (GSH) between 2015 and 2021 using FISH. Methods: FISH for MYC, BCL2, and BCL6 alterations was performed on formalin-fixed paraffin wax-embedded (FFPE) tissue according to manufacturer instructions. Each case was assessed for rearrangement and CNV. Appropriate statistical analyses were conducted to correlate the molecular alterations with histopathological data. The clinical data like prognosis and treatment outcomes for these cases were not available. Results: The patient cohort comprised 75 cases. The age range was between 18 and 83 years with 31 (41.3%) females and 44 (58.7%) males. HIV data was known in 72 cases, with 30/72 patients (41.7%) being HIV positive and 42 (58.3%) being HIV negative. Fifty cases yielded a result with all the FISH probes tested (66.7%). The MYC FISH results comprised 13/50 (26.0%) cases with rearrangement, 9/50 (18.0%) cases with CNV and 28/50 (56.0%) with no aberrations. BCL2 FISH yielded 6/50 (12.0%) cases with rearrangements, 6/50 (12.0%) with CNV and 38/50 (76.0%) with no aberrations. BCL6 FISH yielded 9/50 (18%) cases with rearrangements, 12/50 (24%) with CNV and 29/50 (58.0%) with no aberrations. Using this data, cases were classified resulting in 45/50 (90.0%) DLBCL, NOS cases, 1/50 (2.0%) DLBCL with MYC and BCL2 rearrangement (DHL) and 1/50 (2.0%) DLBCL with rearrangement of MYC, BCL2 and BCL6 (THL). There were 3/50 (6.0%) EBV-positive DLBCL, NOS cases. The DHL and THL cases both were from the GCB subtype. The DLBCL, NOS cases comprised 26/45 (57.8%) GCB and 19/45 (42.2%) non-GCB subtypes. The EBV-positive DLBCL, NOS cases were all non-GCB subtypes. Of statistical significance, 13/47 (27.7%) of HIV-positive cases were of the GCB subtype (P=0.028). Also, 10/28 (35.7%) of the cases with BCL2 aberrations were from the GCB subtype (P=0.029). When the immunohistochemistry (IHC) results were correlated with the FISH results, all cases with BCL2 aberrations were positive for BCL2 IHC expression (P=0.038). Atypical hits were observed in 23/50 (46.0%) cases and in 33/50 (66.0%) of cases, one or more aberrations were present. Conclusion: This was the first study at GSH to investigate the spectrum of MYC, BCL2 and BCL6 gene alterations in a cohort of DLBCLs. The MYC gene was rearranged the most (26.0%) followed by BCL6 (18.0%) and BCL2 (12.0%). The BCL6 gene showed the most copy number variations (24.0%) followed by MYC (18%) and BCL2 (12.0%). These findings were largely consistent with other studies. The effect HIV has on the germinal centre was noted in our study, highlighting the role HIV plays in the development of DLBCL. Although rearrangements and protein expression are frequently co- expressed, MYC, BCL2 and BCL6 IHC as a surrogate for predicting rearrangements cannot be used. Regarding the classification, 90.0% of cases were DLBCL, NOS. DHL and THL were an uncommon finding and while they account for a very low prevalence, they can only be identified by cytogenetic testing in a diagnostic setting. This highlights the invaluable need for FISH as a diagnostic tool in lymphoma classification. In 66.0% of our cases, there was at least 1 MYC, BCL2 or BCL6 aberration present. Only 34.0% of DLBCLs, in this cohort, were without alterations in any of the 3 genes tested. This finding highlights the genetic heterogeneity of DLBCL and reaffirms the role of these oncogenes in the pathogenesis of DLBCLs.